Adsorption Ability and Kinetic of (Congo Red, Methyl Green) Dyes on Iraqi Siliceous Rocks - Israa Mohammed Tawfeeq (Journal of Global Pharma Technology, 2016)
In this study used Iraqi Siliceous Rock powder (SRP) as a suitable surface to study removing of dyes, which are they [Cong red dye (CR) and Methyl green dye (MG)]. Adsorption isotherms and the factors which influence the adsorption process such as temperature and salt effect were studies. Adsorption isotherms of (CR) were found to be comparable to Temkin equation according to Giles classification. Adsorption isotherms of (MG) were found to be comparable to Freundlich equation according to Giles classification. The adsorption process on surface was studies at various temperatures. The results indicate that the adsorption of (CR) on surface decreased with increasing temperature (Exothermic process), while the adsorption of (MG) on surface increased with increasing temperature (Endothermic process). According to above results of thermodynamic functions (ΔG, ΔS, ΔH) were calculated. The salt effect of adsorption of (CR, MG) dyes at (293 K) were studied .The adsorption quantity for (MG) increasing with increasing the salt solution, while the adsorption quantity for (CR) dye decreasing with increasing the salt solution. The Kinetics of adsorption process of (CR, MG) dyes on surface were studied. The results were treated according to (Lagergren equation). The Kinetics experimental data properly correlated with First-order kinetic model.Keywords: Siliceous Rock, Adsorption, Congo red Dye, Methyl Green Dye.